Analyzing the Landscape of Education Management Research: A Bibliometric Analysis of Scholarly Publications on Education Management - Muhammad Ihsan Dacholfany; Tiara Fathulmila Matiala; Sabil Mokodenseho; Gilang Kartika Hanum (Eastasouth Institute, 2023)
Education management is a critical aspect of educational systems, encompassing policies, planning, organization, and leadership. Understanding the research landscape in education management is essential to inform evidence-based practices, guide policymaking, and enhance educational outcomes. This research employs a comprehensive bibliometric analysis using VOSviewer to examine scientific publications on education management. The analysis quantifies scholarly output, identifies influential works and authors, and explores collaboration patterns within the field. Key findings highlight the significance of leadership, education management, and entrepreneurship education as prevalent themes. Moreover, the analysis underscores the growing interest in promoting self-management skills and sustainability in educational contexts. These insights can guide researchers, educators, and policymakers in shaping the future of education management practices and policies.